A Descriptive Catalogue of Eight Medieval Manuscripts from Wadham College, Oxford. (18th December 2020) - Stone, Zachary E
Abstract: Ranging from an eleventh-century Gospel Book to a fifteenth-century copy of John Gower's Confessio Amantis, the medieval manuscripts of Wadham College merit more extensive consideration than they have hitherto received. This article seeks to enable and encourage the continued investigation of Wadham College's manuscript collection by providing preliminary descriptions for eight manuscripts lacking modern descriptions (MSS 1, 2, 5, 9, 11, 12, 13, and 10.19).